Effect of silver nanoparticles on wettability, anti-fungal effect, flexural strength, and color stability of injection-molded heat-cured polymethylmethacrylate in human saliva - W Vaiyshnavi; J Brintha Jei; B Muthu Kumar (Wolters Kluwer Medknow Publications, 2022)
Aim: Aim of this study was to evaluate the effect of silver nanoparticles incorporated injection molded heat-cured polymethylmethacrylate resin on wettability, anti-fungal effect, flexural strength and colour stability in human saliva. Settings and Design: An In-Vitro study with In -Vivo parameter Materials and Methods: Rectangular and circular stainless-steel dies were fabricated according to ISO standardization 20795-1:2018 and ADA specification number 12. A total of 144 samples were prepared and divided into 4 groups with thirty-six samples in each group. Each of the 4 groups were subdivided into 3 subgroups based on concentration of silver nanoparticles as 0% in subgroup A, 0.05% in subgroup B and 0.2% in subgroup C. Group 1 samples evaluated wettability, they were assessed at 0, 7, 90 and 180 days after immersing in human saliva using goniometer. Group 2 samples evaluated antifungal effect, they were assessed against Candida albicans in Muller hinton agar plate enriched with 2% glucose. Group 3 samples evaluated flexural strength, they were assessed by using universal testing machine. Group 4 samples evaluated colour stability, they were assessed using UV spectrophotometer at 0, 3 and 7 days after immersing in human saliva. Statistical Analysis Used: One-way ANOVA and Post- Hoc Tukey test were used to evaluate the significant differences in the mean values of the groups. Results: Subgroup C samples with 0.2% Ag nanoparticles had better wettability, maximum antifungal property, highest flexural strength and good colour stability followed by subgroup B and subgroup A samples. Conclusion: Injection molded denture base resin incorporated with 0.2% Ag nanoparticles could be used clinically as a denture base material for completely and partially edentulous patients.